Mainstreaming video games: A cultural response - Hossain, Syed Arman; Fahad, Abdullah Al (International Journal of Emerging Trends in Social Sciences, 2024)
This paper examines the integration of video games into Dhaka’s cultural landscape in Bangladesh, considering the impact of sociocultural and economic factors. Through ethnographic research and the application of theoretical frameworks such as the theory of attainment, this study investigates the factors contributing to the popularity of video games in Dhaka. The research explores how vocational expectations in education and a focus on specific career outcomes shape the cultural narrative surrounding video games. Video games serve as sources of entertainment and social validation, filling the void created by limited recreational spaces and changing social norms. The commercial aspect of video games also facilitates peer bonding and social interaction, aligning with the prevailing neoliberal ethos in Dhaka’s society. The theory of attainment helps explain the motivations underlying the widespread adoption of video games, linking it to the pursuit of predefined objectives within the neoliberal paradigm. As Dhaka undergoes neoliberal transformations, video games have become central to its cultural landscape, functioning as coping mechanisms and sources of identity and connectivity in the face of limited leisure spaces and changing social configurations. This article seeks to understand the popularity of video games in Dhaka by exploring the interplay of culture, technology, and socioeconomic factors. It presents video games as both reactions to and reflections of the city’s evolving environment, shedding light on the dynamics shaping leisure practices in urban Bangladesh. This research can contribute to further investigations and studies on online gaming within the sociocultural context of Bangladesh.